Microbial translocation in HIV infection: causes, consequences and treatment opportunities - Sandler, Netanya G.; Douek, Daniel C. (Nature reviews. Microbiology, 2012)
Key Points Individuals with HIV infection have increased translocation of commensal microbial products, such as lipopolysaccharide (LPS), from the intestinal lumen into the systemic circulation. Increased translocation of pro-inflammatory microbial products in HIV infection may be caused by enterocyte death, loss of tight junctions between enterocytes, decreased intestinal lumen immunoglobulin A (IgA), loss of CD4 + T cells (especially T helper 17 cells) from gut-associated lymphoid tissue, alterations in intestinal flora and decreased clearance of microbial products by the liver and other mechanisms. Rhesus macaques infected with SIV (a virus similar to HIV) show persistent intestinal damage, increased microbial translocation and increased immune activation, and the infection eventually progresses to AIDS. Conversely, sooty mangabees infected with SIV do not show persistent intestinal damage, increased microbial translocation or increased immune activation, and they do not develop AIDS. In individuals infected with HIV, increased levels of LPS and/or soluble CD14 (sCD14), which reflects LPS-induced monocyte activation, correlate with numerous markers of immune activation, such as type I interferons and activated CD8 + T cells (the latter being one of the strongest predictors of disease progression in HIV infection). Microbial translocation has also been associated with lymphoid tissue fibrosis, which may impair CD4 + T cell recovery in patients on antiretroviral therapy. An increase in sCD14 levels is a predictor of dementia, hypertension, low CD4 + T cell recovery on antiretroviral therapy and, most notably, mortality. Numerous therapeutic options for decreasing microbial translocation and its downstream effects are currently under investigation. Even when receiving antiretroviral therapy, HIV-infected individuals have an increased risk of mortality owing to systemic immune activation. Sandler and Douek review evidence showing that the translocation of microbial products from the intestine into the circulation may contribute to this risk and discuss potential therapeutic strategies. Systemic immune activation is increased in HIV-infected individuals, even in the setting of virus suppression with antiretroviral therapy. Although numerous factors may contribute, microbial products have recently emerged as potential drivers of this immune activation. In this Review, we describe the intestinal damage that occurs in HIV infection, the evidence for translocation of microbial products into the systemic circulation and the pathways by which these products activate the immune system. We also discuss novel therapies that disrupt the translocation of microbial products and the downstream effects of microbial translocation.